Quarterly GDP Estimates for the German States: New Data for Business Cycle Analyses and Long-Run Dynamics - Robert Lehmann; Ida Wikman (Center for Economic Studies and ifo Institute (CESifo), 2023)
To date, only annual information on economic activity is published for the 16 German states. In this paper, we calculate quarterly regional GDP estimates for the period between 1995 to 2021, thereby improving the regional database for Germany. The new data set will regularly be updated when quarterly economic growth for Germany becomes available. We use the new data for an in-depth business cycle analysis and to estimate long-run growth dynamics. The business cycle analysis reveals large heterogeneities in the duration and amplitudes of state-specific fluctuations as well as in the degrees of cyclical concordance. Long-run trends are found to vary tremendously, with positive developments in economically strong regions and flat or even negative trends for economically much weaker states.
Keywords: C32; C53; E32; R11; 330; regional economic activity; mixed-frequency Vector Autoregression; regional business cycles; concordance; Bayesian methods